2019
DOI: 10.3390/jcdd6030031
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) Gene Polymorphism Increases a Risk Factor for Aortic Valve Calcification

Abstract: Calcific aortic valve disease (CAVD) is a multifactorial condition. Both environmental andgenetic factors play an important role in its etiology. CAVD exhibits a broad spectrum, varying frommild valve thickening to severe valve calcification and stenosis. Progression of the disease consistsof chronic inflammation, lipoprotein deposition, and active leaflet calcification. It is a process similarto coronary artery disease. In this study, we investigated Lp(a) levels and gene polymorphismsassociated with calcific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Plasma Lp(a) concentration is primarily (more than 90%) genetically determined by variation in the LPA locus, which encodes the apo(a) component of Lp(a) in the hepatocytes. In particular, the two single nucleotide polymorphisms (rs10455872 and rs3798220) responsible for genetically increased Lp(a) levels have been strongly associated with AV calcification, risk of coronary artery disease, and clinical CAVS, reaching genome-wide significance [43,44]. Very recently, Lp(a) levels have been correlated to AV microcalcification in patients without known CAVS and it has been proposed to measure this parameter in subjects with high Lp(a) levels to detect early events of CAVS before the onset of clinically manifested disease [45].…”
Section: Current Evidencementioning
confidence: 99%
“…Plasma Lp(a) concentration is primarily (more than 90%) genetically determined by variation in the LPA locus, which encodes the apo(a) component of Lp(a) in the hepatocytes. In particular, the two single nucleotide polymorphisms (rs10455872 and rs3798220) responsible for genetically increased Lp(a) levels have been strongly associated with AV calcification, risk of coronary artery disease, and clinical CAVS, reaching genome-wide significance [43,44]. Very recently, Lp(a) levels have been correlated to AV microcalcification in patients without known CAVS and it has been proposed to measure this parameter in subjects with high Lp(a) levels to detect early events of CAVS before the onset of clinically manifested disease [45].…”
Section: Current Evidencementioning
confidence: 99%
“…There is indeed an increase in Lp(a) levels in patients with CAVD. Ozkan et al, (2019) found that the Lp(a) level in CAVD was 68.67 ± 1.5 mg/dl, and 27.05 ± 1.19 mg/dl in the control group. But the prevalence of elevated Lp(a) in patients with established CAVD is unclear now.…”
Section: Introductionmentioning
confidence: 83%
“…Calcific aortic valve disease is a multifactor condition and a dynamic process similar to atherosclerosis. Endothelial cell dysfunction followed by subendothelial accumulation of lipoproteins and chronic inflammation results in a condition that can vary from mild valve thickening to severe calcification with stenotic occlusion [ 36 ]. Studies have shown that Lp(a) levels ≥ 30 mg/dL represent a risk factor for calcific aortic valve disease.…”
Section: Lipoprotein(a) and Atherosclerosismentioning
confidence: 99%
“…Lp(a) contributes to this disease at different rates, which depend on ethnicity [ 9 ], with the highest levels of Lp(a) in calcific aortic valve disease seen for Caucasians [ 9 , 37 , 38 ]. There is also an association between Lp(a) gene polymorphisms and calcific aortic valve disease [ 36 , 38 , 39 , 40 ]. Thanassoulis et al and Ozkan et al showed strong positive correlations for rs10455872 and rs3798220 polymorphisms with the progression of calcific aortic valve disease [ 36 , 40 ].…”
Section: Lipoprotein(a) and Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation